ANALISIS EVALUASI PEMBELAJARAN MATEMATIKA BERBASIS MODEL CIPP DI SEKOLAH MENENGAH KEJURUAN - Siswanto, Deny Hadi; Tarso, Tarso; Susetyawati, M.M. Endang (Jurnal Lingkar Mutu Pendidikan, 2025)
This study aims to evaluate the mathematics learning program at SMK Muhammadiyah Kalasan using the CIPP model (Context, Input, Process, Product). The research subjects consisted of three groups of respondents: educators and policymakers (4 individuals), educational staff (3 individuals), and students (121 individuals). The instrument employed was a questionnaire comprising 30 items. Data were analyzed through score calculation, percentage conversion, and categorization based on evaluation criteria. The findings indicate that the Product component obtained the highest scores across all groups, namely 95.00% (educators), 93.33% (educational staff), and 93.30% (students), reflecting excellent student learning outcomes. However, the Input component, particularly human resources and infrastructure, received lower scores, categorized as good. These results highlight that although learning outcomes are already optimal, further improvements in teacher competence, more systematic instructional planning, and strengthened facilities are still required. Thus, reinforcing the Input and Process components becomes a crucial strategy to ensure the sustainability of mathematics learning quality at SMK Muhammadiyah Kalasan